2020
DOI: 10.1186/s12957-020-01951-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of various criteria for lymph node staging in ductal adenocarcinoma of the pancreatic head by computed tomography and magnetic resonance imaging

Abstract: Background: Lymph node staging of ductal adenocarcinoma of the pancreatic head (PDAC) by cross-sectional imaging is limited. The aim of this study was to determine the diagnostic accuracy of expanded criteria in nodal staging in PDAC patients. Methods: Sixty-six patients with histologically confirmed PDAC that underwent primary surgery were included in this retrospective IRB-approved study. Cross-sectional imaging studies (CT and/or MRI) were evaluated by a radiologist blinded to histopathology. Number and siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
1
21
1
Order By: Relevance
“…The pathological tumor grade was significantly higher in the ER group as well as the clinical staging. The concordance rate between preoperative diagnosis (cTS, cLNM) and pathological diagnosis (pTS, pLNM) is 52.7% and 56.4% respectively, which is consistent with the previous reports [ 28 , 29 ]. The proportion of patients who received adjuvant therapy and R0 resection, which may affect the outcomes, was not different between the two groups.…”
Section: Resultssupporting
confidence: 91%
“…The pathological tumor grade was significantly higher in the ER group as well as the clinical staging. The concordance rate between preoperative diagnosis (cTS, cLNM) and pathological diagnosis (pTS, pLNM) is 52.7% and 56.4% respectively, which is consistent with the previous reports [ 28 , 29 ]. The proportion of patients who received adjuvant therapy and R0 resection, which may affect the outcomes, was not different between the two groups.…”
Section: Resultssupporting
confidence: 91%
“…However, neither EUS nor PET/CT yield sufficient diagnostic accuracy and reliability for the evaluation of the nodal status. 8,10 Radiomics has recently emerged, a technique that can potentially transform original monochrome images into quantitative features using high-throughput extraction methods. Previous studies have indicated that radiomic features are closely linked to patients' prognosis and underlying genomic phenotyping across a wide range of cancer types.…”
mentioning
confidence: 99%
“…Criteria for lymph node configuration also exist with numerous descriptors, which can sometimes be helpful [ 5 8 ]. There have been some promising approaches by combining size and configuration criteria to facilitate and standardize the diagnostic workup for lymph nodes at specific anatomic locations, such as in the mesorectum in a European Society of Gastrointestinal and Abdominal Radiology (ESGAR) consensus statement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%